The Effect of Campus Environment towards the Learning Motivation - Vinny Stephanie Hidayat; Debbianita debbianita; I Nyoman Agus Wijaya; Sherin Ivana Dewi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2021)
The aim of this research is to determine the effect of Campus Environment (Physical and Non-Physical Environment) towards the learning motivation of students at Maranatha Christian University. The population of this research is the whole of accounting students at Maranatha Christian University. The sample of this research is 91 accounting students at Maranatha Christian University. The method used in this research is explanatory research, and the sampling method used is judgment sampling method. T-test and F test are used for Research hypothesis testing and SPSS version 20.0 is used for multiple regression analysis. The result of this research shows that College Environment affects the student’s motivation of studying, thus, the hypothesis of this research is empirically supported.Keywords: campus environment, motivation of studying, internet Access, physical and non-physical environment